Optical Flow Sensor with Fluorescent-Conjugated Hyperelastic Pillar: A Biomimetic Approach - Dongmin Seo; Seungmin Yoon; Jaemin Park; Sangwon Lee; Seungoh Han; Sung-Hoon Byun; Sangwoo Oh (Biomimetics)
Although the Doppler velocity log is widely applied to measure underwater fluid flow, it requires high power and is inappropriate for measuring low flow velocity. This study proposes a fluid flow sensor that utilizes optical flow sensing. The proposed sensor mimics the neuromast of a fish by attaching a phosphor to two pillar structures (A and B) produced using ethylene propylene diene monomer rubber. The optical signal emitted by the phosphor is measured using a camera. An experiment was conducted to apply an external force to the reactive part using a push–pull force gauge sensor to confirm the performance of the proposed sensor. The optical signal emitted by the phosphor was obtained using an image sensor, and a quantitative value was calculated using image analysis. A simulation environment was constructed to analyze the flow field and derive the relationship between the flow rate and velocity. The physical properties of the pillar were derived from hysteresis measurement results, and the error was minimized when pillar types A and B were utilized within the ranges of 0–0.1 N and 0–2 N, respectively. A difference in the elastic recovery characteristics was observed; this difference was linear based on the shape of the pillar, and improvement rates of 99.585% and 99.825% were achieved for types A and B, respectively. The proposed sensor can help obtain important information, such as precise flow velocity measurements in the near field, to precisely navigate underwater unmanned undersea vehicles and precisely control underwater robots after applying the technology to the surface of various underwater systems.